METODOLOGI TAFSIR AMINA WADUD DALAM MENAFSIRKAN AL-QUR’AN - Dedi Junaedi; Muhammadong Muhammadong; Sahliah Sahliah (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
AbstractThe concept of Aminah Wadud in interpreting the Koran is an idea inspired by Fazlur Rahman which has a neo-modernist orientation in order to find a hermeneutic-based theory. The concept of gender is a theory developed by Amina Wadud so that women's equal rights run in a balanced way with men's rights. The main consideration in hermeneutic-based interpretation, Amina Wadud places more emphasis on the aspect of objectivity rather than the aspect of subjectivity so as to facilitate the interpretation of Qur'anic verses. Amina Wadud is more inclined to general principles in contextualizing the understanding of the Koran because it can be more easily understood than textualization because the urgency of the Koran was revealed not based on the text of the verse but seeing the conditions that occur in the field by looking at the character of society. Keywords: Methodology; Commentary; Amina Wadud. AbstrakKonsep Amina Wadud dalam menafsirkan Al-Qur’an merupakan gagasan yang diinspirasi dari fazlu Rahman yang berhaluan neo modernis dalam rangka menemukan teori berbasis hermenuetika. Konsep gender merupakan teori yang dikembangkan Amina Wadud supaya hak persamaan perempuan berjalan secara berimbang dengan hak laki-laki. Yang menjadi pertimbangan utama dalam interpretasi berbasis hermenuetika, Amina Wadud lebih menekankan pada aspek obyektivitas bukan aspek subyektivitas sehingga memudahkan dalam interpretasi ayat-ayat Al-Qur’an. Amina Wadud lebih cendrung kepada prinsip umum dalam mengkontekstualisasi pemahaman Al-Qur’an karena dapat lebih mudah dipahami dibanding tekstualis karena urgensi diturunkannya Al-Qur’an bukan berdasarkan teks ayat akan tetapi melihat kondisi yang terjadi dilapangan dengan melihat karakter masyarakat. Kata Kunci: Metodologi; Tafsir; Amina Wadud.